Influence of random and designed porosities on 3D printed tricalcium phosphate-bioactive glass scaffolds - Bose, Susmita; Bhattacharjee, Arjak; Banerjee, Dishary; Boccaccini, Aldo R.; Bandyopadhyay, Amit (Additive Manufacturing, 2021)
Calcium phosphate (CaP)-based ceramics are a popular choice for bone-graft applications due to their compositional similarities with bone. Similarly, Bioactive glass (BG) is also common for bone tissue engineering applications due to its excellent biocompatibility and bone binding ability. We report tricalcium phosphate (TCP)-BG (45S5 BG) composite scaffolds using conventional processing and binder jetting-based 3D printing (3DP) technique. We hypothesize that BG's addition in TCP will enhance densification via liquid phase sintering and improve mechanical properties. Further, BG addition to TCP should modulate the dissolution kinetics in vitro. This work's scientific objective is to understand the influence of random vs. designed porosity in TCP-BG ceramics towards variations in compressive strength and in vitro biocompatibility. Our findings indicate that a 5 wt% BG in TCP composite shows a compressive strength of 26.7 ± 2.7 MPa for random porosity structures having a total porosity of 47.9%. The same composition in a designed porosity structure shows a compressive strength of 21.3 ± 2.9 MPa, having a total porosity of 54.1%. Scaffolds are also tested for their dissolution kinetics and in vitro bone cell materials interaction, where TCP-BG compositions show favorable bone cell materials interactions. The addition of BG enhances a flaky hydroxycarbonate apatite (HCA) layer in 8 weeks in vitro. Our research shows that the porous TCP- BG scaffolds, fabricated via binder jetting method with enhanced mechanical properties and dissolution properties can be utilized in bone graft applications.
CRIS-Team Scopus Importer:2021-03-19
Keywords: 3D printing; Bioactive glass; Cytocompatibility; In vitro dissolution; Scaffolds